Heteroepitaxial Integration of Mid-Infrared InAsSb Light Emitting Diodes on Silicon - Evangelia Delli; Peter D. Hodgson; Eva Repiso; Adam P. Craig; Jonathan P. Hayton; Qi Lu; Andrew R. J. Marshall; Anthony Krier; Peter J. Carrington (IEEE Photonics Journal)
Silicon photonics has emerged as the most promising technology for next-generation compact optoelectronic systems, but further development is still required to achieve efficient and reliable on-chip light sources. Direct epitaxial growth of antimonide-based compound semiconductor materials on silicon provides a pathway toward the monolithic integration of new, mid-infrared solid-state light sources and comprehensive photonic circuits on silicon platforms. Such devices have wide-ranging applications in environmental monitoring and medical diagnostics. This paper reports on the realization of a mid-infrared InAsSb light emitting diode directly integrated onto silicon using molecular beam epitaxy. The heteroepitaxial integration of the InAsSb p-i-n device onto silicon was achieved with the use of a novel, antiphase domain-free, GaSb-on-silicon buffer layer. The device exhibited efficient light emission at room temperature, peaking at around 4.5 μm, which corresponds well to the CO2 atmospheric absorption band. An output power of 6 μW and an external quantum efficiency of 0.011% was measured at 300 K. These results demonstrate mid-infrared III-V light emitting diodes can be directly grown on silicon, which is an essential step towards the realization of the next generation, on-chip integrated light sources.